What is carbon? Conceptualising carbon and capabilities in the context of community sequestration projects in the global South. (24th September 2015) - Twyman, Chasca; Smith, Thomas Aneurin; Arnall, Alex
<x xml:space="preserve">Abstract</x> Carbon has been described as a 'surreal commodity.' While carbon trading, storage, sequestration, and emissions have become a part of the contemporary climate lexicon, how carbon is understood, valued, and interpreted by actors responsible for implementing carbon sequestration projects is still unclear. In this review paper, we are concerned with how carbon has come to take on a range of meanings. In particular, we appraise what is known about the situated meanings that people involved in delivering, and participating in, carbon sequestration projects in the global South assign to this complex element. There has been some reflection on the new meanings conferred on carbon via the neoliberal processes of marketisation and on how these processes interact with historical and contemporary narratives of environmental change. But less is known about how these meanings are (re)produced and (re)interpreted locally. We review how carbon has been defined both as a chemical element and as a tradable, marketable commodity. We discuss the implications these global meanings might have for situated understandings, particularly linked to climate change narratives, among communities in the global South. We consider how the concept of carbon capabilities, alongside theoretical notions of networks, assemblages, and local knowledges of the environment and nature, might be useful in beginning to understand how communities engage with abstract notions of carbon. We discuss the implications of specific values attributed to carbon, and therefore to different ecologies, for wider conceptualizations of how nature is valued, and climate is understood. We review in particular how this may impact on community interactions with carbon sequestration projects. Knowing more about how people understand, value, and know carbon allows policies to be better informed and practices more effectively targeted at engaging local populations meaningfully in carbon‐related projects. WIREs Clim Change 2015, 6:627–641. doi: 10.1002/wcc.367 For further resources related to this article, please visit the WIREs website.